PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATERI BANGUN RUANG SISI DATAR - Maman Sri Suganda; Syariful Fahmi (LPPM-Universitas Muhammadiyah Banjarmasin, 2020)
This study aims to produce Augmented Reality-based math learning media to help students overcome problems in learning mathematical material, especially on the material of a solid geometry that requires more visualization to understand it. This research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Researchers carried out the implementation phase of students in class VIII G in SMP Negeri 1 Pleret Bantul. The instruments used by researchers are questionnaires for media experts, questionnaires for material experts and student questionnaire responses. The results of this research are researchers successfully to develop the learning media of build a solid geometry based on Augmented Reality in the form of applications that can be run through students' smartphones. From the research results obtained material assessment by material experts at 88.6%, media assessment by media experts at 95.3%, the response of test class students (five students) by 85.0%, the response of large class students get a percentage amounted to 78.6%, and the average percentage of all assessments was 86.9%. The percentage shows that the learning media that researchers have developed is very feasible to be used in helping students learn the material of build a solid geometry.